PTSD Is Associated with Self-Perceived Hearing Handicap: An Evaluation of Comorbidities in Veterans Without Measured Hearing Loss - Jedlicka, David P.; Zhen, Leslie Q. (Journal of the American Academy of Audiology, 2023)
Background Cases of self-reported hearing difficulty despite no traditionally measured hearing loss (pure tone audiometric thresholds ≤ 25 dB HL from 250 Hz through 8000 Hz) have risen with the return of Veterans from recent conflicts in Operation Enduring Freedom, Operation Iraqi Freedom, and Operation New Dawn. Auditory outcomes improved despite low compliance among those receiving treatment. Medical chart data appeared more comprehensive for Veterans with, rather than without, auditory complaints. One possibility is that self-reported hearing problems are associated with a subset of these comorbidities, the treatment of which improved auditory outcomes.Purpose This study examined the relationships between Veterans' self-reported auditory problems and other diagnosed medical conditions.Research Design A retrospective chart review was used.Study Sample Participants were 286 Veterans, aged 21 to 52 years with pure-tone audiometric thresholds ≤ 25 dB HL at all measured frequencies in both ears. Veterans were dichotomized into a group with either self-reported hearing complaints (n = 143) or an age-matched control group with no auditory complaints (n = 143).Data Collection and Analysis A query of the Computerized Patient Record System was performed with the date range restricted to 2009 to 2018. Metrics of self-perceived hearing handicap, auditory processing disorder testing, and hearing aid use were collected. All diagnoses and related symptoms were recorded. A best subsets regression with principled model selection was performed to investigate the role of these comorbidities on self-perceived hearing loss.Results The self-report group had 16 comorbidities that were classified as prevalent, having occurred in ≥33.3% of the group, compared with the age-matched control group, which had 2 comorbidities. The number of diagnosed medical conditions was associated with self-perceived hearing impairment. Specifically, posttraumatic stress disorder (PTSD) and related symptom clusters constituted the largest group of comorbidities that were significantly associated with self-reported hearing problems.Conclusions The significant association between PTSD and self-perceived hearing impairment warrants investigations on whether treatment of PTSD would reduce perceived hearing handicap severity. Further, PTSD assessments could be useful for audiologists to identify potential candidates for auditory complaints without measured hearing loss.
Keywords: auditory processing disorder; hidden hearing loss; comorbidities; Veterans; posttraumatic stress disorder; traumatic brain injury